Sex differences in healthy brain aging are unlikely to explain higher Alzheimer’s disease prevalence in women - Anne Ravndal; Anders M. Fjell; Didac Vidal-Piñeiro; Øystein Sørensen; Emilie S. Falch; Julia Kropiunig; Pablo F. Garrido; James M. Roe; José-Luis Alatorre-Warren; Markus H. Sneve; David Bartrés-Faz; Alvaro Pascual-Leone; et al. (Proceedings of the National Academy of Sciences, 2025)
As Alzheimer’s disease (AD) is diagnosed more frequently in women, understanding the role of sex has become a key priority in AD research. However, despite aging being the primary risk factor for AD, it remains unclear whether men and women differ in the extent of brain decline with age. Using 12,638 longitudinal brain MRIs from 4,726 participants aged 17 to 95 y across 14 cohorts, we examined sex differences in structural brain changes over time, controlling for differences in head size. Men showed greater cortical thickness (CT) decline in the cuneus, lingual, parahippocampal, and pericalcarine regions; surface area decline in the fusiform and postcentral regions; and in older adults, greater subcortical decline in the caudate, nucleus accumbens, putamen, and pallidum. In contrast, women only showed greater surface area decline in the banks of the superior temporal sulcus and greater ventricular expansion in older adults. These results suggest that sex differences in age-related brain decline are unlikely to contribute to the higher AD diagnosis prevalence in women, necessitating research into alternative explanations.